The Effect of 12 Weeks of Functional Exercises on Forwarding Head Angle and Spirometry Parameters - Faranak Amirkhani; Amirhosein Barati; Maliheh Hadadnezhad; Seyed Sadredin Shojaedin (Vesnu Publications, 2018)
Introduction: Forward head posture (FHP) is one of the most common abnormalities of postures which leads to improper alignment of the neck and shoulder mutual muscles, and make it difficult to breathe properly. The aim of the current study was to evaluate the effect of 12 weeks of functional exercises on forward head posture and spirometry parameters. Materials and Methods: In this quasi-interventional study, 40 patients with forwarding head posture angle of greater than 46 degrees were selected purposefully. They were randomly divided into two equal groups of control and experimental. Before and after 12 weeks functional exercises, forward head posture was assessed using the lateral view image and calculating forward head angle (angle between vertical line and the line between the tragus and C7); spirometry parameters were noted, too. The research findings were analyzed using descriptive and comparative methods at the significant level of less than 0.05. Results: In experimental group, the mean forward head angle was significantly decreased (from 55.25 ± 4.14 to 51.30 ± 4.24 degrees); while respiratory capacity of forced expiratory volume for first second (FEV1) (from 87.50  ±4.50 to 92.95±  4.51 percent), forced vital capacity (FVC) (from 89.05±  6.04 to 94.10  ±4.83 percent), and peak expiratory flow (PEF) (from 86.55 ± 4.08 to 91.65±  4.00 liter/minute) significantly increased (P < 0.001 for all). These changes were not seen in the control group.